The Application of Chitosan as a Natural Flocculant Material to Chlorella sp. Abundance - Dewi Puspaningsih; Eri Setiadi; Lies Setijaningsih; Imam Taufik (Journal Omni-Akuatika, 2022)
Natural feed must be available in order to give high-quality seeds to support aquaculture activities. Chlorella sp. is a natural food source for fish larvae and zooplankton.  Chlorella sp. is more effective and efficient when stored in the form of floc. The purpose of  this research was to obtain an effective dose of chitosan for flocculation of Chlorella sp. The study used a completely randomized design (CRD) with 5 treatments and 3 replications, i.e A. 150 mg L-1, B. 200 mg L-1, C. 250 mg L-1, D. 300 mg L-1, E. 350 mg L-1. The abundance of Chlorella sp. before and after flocculation measured as the main parameter. Water quality parameter such as temperature, pH, dissolved oxygen, total ammonia nitrogen, and nitrite function as supporting parameters. The results showed that the abundance of Chlorella sp. before flocculation increased from the beginning of stocking until the 6th day. The best results of the abundance of Chlorella sp. found in the C treatment (54.4-74.5%), then followed with B, A, D, and E treatments (31.2-55.1%, 22.8-51.2%, 19.0-45.6 %, and 13.3-44.6%) respectively. The most effective dose of chitosan in the flocculation process of fresh water Chlorella sp. was 250 mg L-1 with an abundance of 39.1x105 cells mL-1. Water quality in culture media of the Chlorella sp. showed that the range of measured values were still within the optimum range.Keywords: Abundance, Chitosan, Chorella sp., Flocculation